Categorizing People by Their Preference for Religious Styles: Four Types Derived from Evaluation of Faith Development Interviews. Issue 2 (2nd April 2020) - Streib, Heinz; Chen, Zhuo Job; Hood, Ralph W.
ABSTRACT: This article presents a typology that categorizes people according to their profile of religious styles which concerns, among other things, the sources where they derive validity and stability, when confronted with religious and existential questions or inter-religious challenges. The modeling of this typology is an empirical complement to Streib's model of religious styles which, in turn, is a critical advancement of Fowler's faith development theory. Data are religious style assignments to the answers on the 25 questions in the Faith Development Interview (FDI), which has been administered to 677 participants in the United States and Germany. We present results based on a theory-driven approach to determine a person's religious type by incorporating frequencies of religious style assignments from the evaluation of their FDI. We also explored convergent validity with latent class analysis and a machine-learning algorithm. Results based on three samples converged on four religious types: Substantially Ethnocentric, Predominantly Conventional, Predominantly Individuative-Reflective, and Emerging Dialogical-Xenosophic types. We reported the profiles of the four types with reference to group differences on religious schemata and openness to experience.